Vibration tests of precompressed rubber springs and a flag-shaped smart damper. (1st February 2017) - Choi, Eunsoo; Youn, Heejung; Park, Kyoungsoo; Jeon, Jong-Su
Highlights: Develop a flag-shaped smart damper using magnets and precompressed rubber springs. Perform vibration tests with variation of frictional force and loading frequency. Exhibit good flag-shaped behavior including self-centering and energy dissipation. Rubber springs and magnets are relatively cheaper than shape memory alloys. The proposed smart damper can be applied to a knee brace in building frames. Abstract: The aims of this study were to introduce a smart damper with flag-shaped behavior using friction of magnets and self-centering capacity of precompressed rubber springs and to conduct vibrational tests to verify its performance. A damper exhibiting flag-shaped behavior is considered the most effective to sufficiently provide energy dissipation and self-centering after earthquakes or strong vibrations. The damper suggested in this study used practical materials to realize a smart damper. For these purposes, hexahedron Neodymium (NdFeB) magnets with dimensions of 50 mm × 50 mm × 25 mm (B × L × H) and polyurethane rubber cylinders of 80 mm in length and 80 mm in diameter with a central hole of 20 mm were used. The experimental program in this study consists of three tests; magnetic friction and precompressed rubber springs were first tested separately, and, the damper comprising the two components was tested. For the test of the magnet, two parameters of frictional force and loading frequency were considered. The loading frequency was varied from 0.1 to 2.0 Hz, and the frictional force was controlled by the number of magnets, namely, 0, 4, 8, and 12. From the separating tests, frictional coefficients of magnets of were estimated; the value was 0.65. The rigid force of the rubber springs was assessed according to precompression; the rigid force increased linearly with an increasing strain of precompression up to the strain of 20%. From the rubber tests, the Young's modulus of the polyurethane rubber was estimated as 52.8 MPa, which was much greater than that of natural rubber. The vibration test for a combined damper produced flag-shaped behavior of the damper, and their damping ratios and stiffnesses were assessed from the hysteretic curves. The damping ratio of only rubber springs was 2.78%, and the damping ratios with 12 magnets increased to 7.12%. The estimated stiffness after the rigid behavior was 17.2 kN/mm. The suggested damper showed good performance of flag-shaped behavior.